2010 International Conference on Computational Intelligence and Software Engineering 2010
DOI: 10.1109/cise.2010.5676832
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Trust in E-Government

Abstract: E-governments are increasingly becoming a familiar fixture. Nations across the world are realizing the importance of e-government, the main objective of most e-government is to better serve citizens. howerver, citizen's likelihood to use egovernment is low. Lack of trust has been recognized as one of the most barriers to citizen for engaging in e-government, involving the trust in the internet and the trust in the government. This paper identifies these two main factors that determine citizen trust the e-gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…System quality refers to the performance of the system and its reliability and accessibility. Service quality reflects the citizens' evaluation of the service quality with respect to the service that they actually receive and what they expect (Wang et al, 2010).  Government agencies' factors: the reputation of an agency and past experience are fundamental factors of government agencies (Beldad et al, (2011)).…”
Section: The Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…System quality refers to the performance of the system and its reliability and accessibility. Service quality reflects the citizens' evaluation of the service quality with respect to the service that they actually receive and what they expect (Wang et al, 2010).  Government agencies' factors: the reputation of an agency and past experience are fundamental factors of government agencies (Beldad et al, (2011)).…”
Section: The Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…According to Williams et al, trust in technology is a crucial determinant for the uptake of m-payment service by customers [65]. Trust in the government and the Internet were also the main factors contributing to citizen trust in e-government [84].…”
Section: Legal Advice Servicesmentioning
confidence: 99%
“…A total of 71 research studies (Al‐Rashidi, 2010; Andersen, 2006; Axelsson et al , 2010; Chango, 2007; Hwang et al , 2004; Norris, 2009; Wang and Lu, 2010; Wiredu, 2010) explored the challenges and barriers of e‐government adoption research. This was further broken down into challenges/barriers for implementation of e‐government system (Adeyemo, 2011; Aman and Kasimin, 2011; Chango, 2007; Ni and Ho, 2005; Wang and Hou, 2010) and challenges/barriers for adoption (Berdykhanova et al , 2010; Ray, 2011; Shalini, 2009; Weerakkody and Choudrie, 2005; Wescott, 2004).…”
Section: E‐government Adoption: Challenges and Barriersmentioning
confidence: 99%
“…Wang and Hou (2010) investigated the internal and external barriers to the e‐government implementation and revealed that governmental and regulatory barriers, lack of communication among agencies were some of the external obstacles whereas fast technical change, digital divide, privacy and security, citizen belief and flawless services were some of the internal barriers. Wang and Lu (2010) determined lack of trust as one of the key barriers for citizen participation with e‐government system.…”
Section: E‐government Adoption: Challenges and Barriersmentioning
confidence: 99%